The Burden of Acinetobacter baumannii in the Intensive Care Unit of a Teaching Hospital in Kuwait Over a 3-Year Period. (4th October 2017) - Jamal, Wafaa; Salama, Mona; Shahin, May; Rotimi, Vincent
Abstract: Background: Acinetobacter baumannii is often endemic in several ICUs worldwide. Once it is established, it is difficult to eradicate. This study was undertaken to determine the burden of multi-drug-resistant A. baumannii infections in ICU of Mubarak hospital, Kuwait over 3 years period. Methods: A. baumannii infections/colonization of ICU patients attended by infection prevention (IP) team at our hospital over a period of 3 years, January 2014 to December 2016, were included in the study. Outbreak size, mortality, source and outbreak control measures were carefully recorded. The isolates were identified and tested for their susceptibilities by semi-automated VITEK-2 system. The clonality of the isolates was determined by molecular typing methods using RE--PCR DiversiLab or pulsed-field gel electrophoresis. Results: A total of 164 episodes of infections/colonization was encountered. Of these, 84 (51.2%) were proven cases of sepsis. In 2014, 2015 and 2016, 26/13, 37/32 and 21/35 episodes of infection/colonization, respectively were recorded. During this period, 2 outbreaks each involving 9 and 13 patients in 2014, 3 outbreaks involving 11, 15 and 20 patients in 2015, and 15, and 2 outbreaks of 15 and 9 patients in 2016 were encountered. The main sources of infections/colonization were respiratory (58.5%), BS (23.8%), urinary tract (7.9%), surgical site (6.1%), CSF (1.8%), and intra-abdominal (1.8%). The associated mortality rates were 23.1, 41.6, and 11.3%, respectively. Over 84% of the isolates were multidrug-resistant organisms. Analysis of molecular typing demonstrated clonality only among 5 isolates in 2014, 9 in 2015, and 8 in 2016, with no carry-over of related strains from year to year; the rest were heterogeneous. Despite implementation of stringent infection control measures, such as screening of patients, contact precautions and cohort isolation, enhanced environmental cleaning, limiting of patient transfers, and staff/patient education with emphasis on hand hygiene, A. baumannii persisted in the unit. Conclusion: Our study demonstrates a high burden of A. baumannii in our ICU throughout the 3 years and with outbreaks in between. Programs to improve IP practice and address antibiotic resistance in the ICU are urgently required. Disclosures: All authors: No reported disclosures.